2022
DOI: 10.1177/11206721221126286
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the guidelines for retinopathy of prematurity

Abstract: As the characteristics of preterm infants with retinopathy of prematurity (ROP) vary, depending on the quality of neonatal care they received, universal screening criteria for ROP are not possible. The purpose of this study was to compare ROP guidelines for those planning to develop guidelines, particularly in resource-poor settings. A systematic review was undertaken of PubMed, Embase and guidelines registers to identify national or international policy statements or guidelines in English, issued or operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In general, there has been a tendency to use flexible criteria in low- and middle-income countries (e.g., GA ≤32 or 37), and stricter criteria in high-income countries (e.g., GA ≤30). [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…In general, there has been a tendency to use flexible criteria in low- and middle-income countries (e.g., GA ≤32 or 37), and stricter criteria in high-income countries (e.g., GA ≤30). [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies were eligible for inclusion when (unadjusted) data were reported on HCA with or without FUN in preterm neonates (<37 weeks' GA and/or BW < 2,000 g) with ROP. 11 12 Articles were excluded when the study population consisted entirely of animals or multiple pregnancies due to its confounding effect. 13 Additionally, articles were excluded when placenta reports were unavailable to histologically confirm CA in cases with CCA, which is diagnosed by nonspecific clinical symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Screening for ROP, which should include all eligible infants according to local guidelines, starts within weeks of birth 12. Unlike screening for other conditions, which usually entails a one-off procedure, screening for ROP may need to be repeated at frequent intervals depending on the clinical findings.…”
Section: Introductionmentioning
confidence: 99%